TESIS, ANTITESIS, DAN SINTESIS EKSISTENSI KEMBAR BUNCING DALAM NOVEL INCEST KARYA I WAYAN ARTIKA - I Nyoman Yasa (Universitas Pendidikan Ganesha, 2010)
The aims of this research is to describe thesis, antithesis, and the existence synthesis Kembar Buncingin Incest novel by I Wayan artika. The design of this research is qualitative descriptive by usingstructural approach. This research use Hegel Dialectical Theory. The result of this research show thatthesis, antithesis, and synthesis caused by the differences of customs development in Jelungkap Village.The other researchers should observe this novel from the other aspects, such as feminist actorsby using feminism theory.Key words: thesis, antithesis, synthesis, kembar buncing, incest.